2022
DOI: 10.1186/s13065-022-00909-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical investigation of Ludwigia adscendens subsp. diffusa aerial parts in context of its biological activity

Abstract: Ludwigia adscendens subsp. diffusa (Onagraceae), an important aquatic herb widely distributed in the Nile River and canals in Egypt. The goal of the current study is to investigate the phytochemical composition of L. adscendens aerial parts n-butanol and ethyl acetate fractions and screening of its biological activities. Phytochemical investigation of L. adscendens resulted in the isolation and purification of eleven compounds belonging to flavonoids, saponins, triterpenoids, and oligosaccharides, of which one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 2020 , 2021 ; Baky et al. 2022 ). Studies have shown that during the growth process of L. adscendens , this plant can absorb nutrients in wastewater, and thus play a promising role in improving water pollution (Xu et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“… 2020 , 2021 ; Baky et al. 2022 ). Studies have shown that during the growth process of L. adscendens , this plant can absorb nutrients in wastewater, and thus play a promising role in improving water pollution (Xu et al.…”
Section: Introductionmentioning
confidence: 99%
“…L. adscendens is a perennial floating aquatic herbaceous plant, in the genus Ludwigia of the family Onagraceae, which is commonly known as Water Dragon (Baky et al. 2022 ). L. adscendens are distributed worldwide but are mainly distributed in Asia and are common in southern China.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of traditional applications for Ludwigia species, including anti-inflammatory, antidiarrheal, anti-diabetic and antibacterial symptom alleviating properties. Flavonoids, saponins, phenolic compounds, and triterpenes are only some of the many types of phytochemicals that have been attributed to the Genus Ludwigia's abundance [10]. Quercetin, quercetin 3-O-rhamnoside or quercitrin, quercetin 3-O-galactoside, quercetin 3-O-glucoside, quercetin 3-O-rutinoside, kaempferol 3-Oglucoside, myricetin 3-O-rhamnoside or myricitrin, and myricetin 3-O-galactoside have all been identified as being present in Ludwigia adscendens [11].…”
Section: Introductionmentioning
confidence: 99%